Foreign Authors’ Enforcement of U.S. Reversion Rights - Ginsburg, Jane C. (The Columbia Journal of Law & the Arts, 2018)
Thank you to all of the participants, and especially the first two panelists, for setting one part of the scene. I am going to talk about the United States’ termination right and some Berne and private international law consequences or implications of the termination right. First, however, I’d like to advert to the two goals Rebecca Giblin referenced in her talk. One is remuneration, the other is dissemination. Author-protective laws in other countries also address dissemination. As Séverine Dusollier mentioned, a number of national laws include an obligation to exploit the work: if the publisher does not exploit the work, the rights revert to the author. In the United States, the contractual out-of-print clause serves that purpose, but the out-of-print clause is a matter of private ordering. It has to be activated by the author and publishers lately have contended that as a result of print-on-demand, the work never goes out of print. If the book is available in the catalog, and somebody at some point wants a copy, then the publisher can provide that copy. Out of print clauses in the digital environment therefore, some publishers would argue, make no sense. Mary Rasenberger accordingly mentioned some of the attempts of the Author’s Guild to push back against the disappearance of the out-of-print clause. The rest of my remarks will concern remuneration, rather than dissemination. As both Martin Senftleben and Séverine Dusollier pointed out, there exists a disparity in bargaining power: authors generally are the weaker party. Two broad techniques seek to remedy this problem. Previous speakers have addressed one of them, intervention by national laws with respect to the amount that the author gets paid, and with respect to the scope of the grant. Thus, in some countries, as Séverine Dusollier mentioned, the law prohibits the author’s grant of modes of exploitation unknown at the time of the contract. These laws effectively reserve new technology rights to the author. Other national laws require additional remuneration for new modes of exploitation, or for “bestsellers” whose authors’ remuneration becomes excessively disproportionate to the grantees’.